2019
DOI: 10.1111/ajd.13103
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous presentation of a granular cell tumour in scar tissue

Abstract: cobblestone-patterned plaque, and the histology was similar to that of fibroelastolytic papulosis.The pathogenesis of fibroelastolytic papulosis is unknown. Ultraviolet radiation from sun exposure may be less likely in the light of some rashes in sun-protected areas. Intrinsic ageing does not seem to be the only cause, because some cases have been reported in patients as young as 28 years. 3 Genetic and hormonal factors have also been considered because of a few familial cases reported as well as the predilec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A variety of lesions can occur at the surgical scar site, including traumatic neuromas, sarcomas, and desmoid tumors, 2 and the case presented here adds GCT to this list. Given the fact that these lesions may not be differentiated clinically, histopathology and immunohistochemistry are necessary to establish the diagnosis.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…A variety of lesions can occur at the surgical scar site, including traumatic neuromas, sarcomas, and desmoid tumors, 2 and the case presented here adds GCT to this list. Given the fact that these lesions may not be differentiated clinically, histopathology and immunohistochemistry are necessary to establish the diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…So far, only rare cases of GCT have been reported developing at skin trauma sites, either the site of vaccination or surgical incision. 2 , 3 , 4 , 5 , 6 Murcia et al 5 published the first case of GCT occurring on the vulvar episiotomy scar presenting as a subcutaneous nodule found during a routine gynecologic examination. In another case reported by Sułkowski et al, 6 GCT was found on a cesarean section scar at the fascia level, mimicking an endometrial tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several other reports of GCTs developing in sites of previous localized trauma, including 2 cases of GCTs developing at vaccination sites and several cases of GCTs occurring at previous surgical sites. [6][7][8][9] In these cases, the temporal relationship between the traumatic insult and the development of the GCT varied between 2 weeks and greater than 8 years. Although none of the previous reported cases developed as far removed temporally from the initial dermal trauma as in our patient, it is possible that the chronic scar tissue or inflammation caused by the tattoo placement predisposed the patient to development of a GCT.…”
Section: Discussionmentioning
confidence: 99%